Electrochemical generation of arsenic volatile species using a gold mercury amalgaman cathode. Determination of arsenic by atomic absorption spectrometry. - Romero Bonilla, Hugo (Netherlands, 2015)
The electrochemical generation of arsenic volatile species (arsine) using an Au/Hg amalgam cathode in a 0.5 M H2SO4 solution, is described. Results were compared with those obtained with other cathodes commonly used for generation of arsine. The effects of the electrolytic conditions and interferent ions have been studied. Results show that the Au/Hg cathode has better tolerance to interference and higher repeatability than cathodes made out of platinum (Pt), gold (Au), reticulated glassy carbon (RGC), lead (Pb). Under optimized conditions, a 0.027 μg L−1 (3σ) detection limit for As(III) in aqueous solutions and a 2.4% relative standard deviation for a 0.1 μg L−1 As(III) were obtained. The accuracy of the method was verified by determination of As in a certified reference material. The proposed method was applied to the determination of As in spiked tap water samples.
Keywords: ANALYTICAL CHEMISTRY RESEARCH; GENERACION DE HIDRURO DE ARSENICO ELECTROQUIMICA; ESPECTROMETRIA DE ABSORCION ATOMICA; MUESTRAS DE AGUA DE GRIFO